SPECT findings on neuropsychiatric symptoms caused by nitrous oxide abuse - Wang, Li; Yin, Lijie; Wang, Qian; Wang, Renbin; Liu, Zunjing; Dong, Mingrui; Duan, Xiaohui; Zheng, Yumin; Hong, Wen; Liu, Fang; Tie, Changle (Frontiers in Psychiatry, 2022)
Objective: To investigate the clinical, neuropsychological and changes of regional cerebral blood flow (rCBF) perfusion in patients with neuropsychiatric symptoms caused by nitrous oxide (N2O) abuse. Method: Sixteen patients with neuropsychiatric symptoms caused by nitrous oxide abuse were recruited. The study was done in withdrawal phase of N2O abuse. 925-1110 MBq 99mTc-ECD was administered intravenously. The SPECT/CT images were collected with low-energy and high-resolution collimator. The region uptake statistics of different brain regions of interest between patients with N2O abuse and normal people of the the databases for younger subjects from the Scenium DB Comparison software were calculated automatically. Results: The clinical manifestations of the 16 patients with neuropsychiatric symptoms were mood lability, anxiety, hallucination, delusion, agitated, confusion, and other psychiatric symptoms. In addition, 15 patients of them also complained their memory decline. 14 patients manifested as numbness or paresthesias. 14 patients developed limb weakness, whose motor impairments were more severe in lower limbs than upper limbs. 8 patients also accompanied by urinary and defecation disturbance. Neuropsychological examination: BPRS score was 54.69±11.48, the score of HAMD was 30.00 ± 11.06, the score of HAMA was 18.06 ± 5.77, the score of MMSE was28.06 ± 2.29, and the score of MoCA was 25.06 ± 3.40. SPECT showed hypoperfusion in the frontal lobe and the temporal lobe, which consistent with the clinical findings. Conclusions: It was the first study to demonstrate obvious effect of N2O abuse on CBF in patients with neuropsychiatric symptom. CBF perfusion imaging is helpful to detect the changes of local brain functional activity in patients with N2O abuse.